Relationship between Musculoskeletal Disorders and Ergonomic Working Conditions in Nurses - Jovilė Džervė; Anelė Katinė (Lithuanian Sports University, 2024)
Background. Nurses experience a higher prevalence of musculoskeletal disorders compared to other healthcare professions. Identifying unsafe work environments and mitigating ergonomic risk factors are crucial steps toward creating a safer workplace for nurses. The aim. To analyze the prevalence of musculoskeletal disorders and assess ergonomic working conditions among nurses. Methods. Fifty-one nurses, working a minimum of 40 hours per week in a patient care facility, participated in the study. Respondents completed a questionnaire covering musculoskeletal disorder prevalence (four questions) and ergonomic work factors (27 questions). Results. In the past 12 months, 84.3% of respondents reported lower back pain, 72.5% experienced neck pain, 64.7% reported shoulder pain, 62.7% reported upper back pain, and 58.8% reported knee and ankle pain. While 84.3% of nurses indicated having adequate equipment for patient transfer and transportation, 23.5% reported not always knowing how to use assistive devices. Conclusions. Lower back pain is the most reported issue among nurses, followed by neck pain. Nurses often face physically demanding tasks when working with patients, frequently involving repetitive movements or tasks. Keywords: ergonomics, working conditions for nurses, musculoskeletal disorders.